Kreativitas Guru dalam Mengembangkan Potensi Kognitif Siswa pada Pembelajaran PAI - St. Aisyah (IQRO: Journal of Islamic Education, 2018)
This study aims to: describe what creativity and effort should be done by teachers in developing cognitive potential. This research is a descriptive study, using a qualitative approach. Data collection is done by making observations, in-depth interviews, and documentation. Subjects and objects in this study were teachers of Palopo Muhammadiyah Middle School, Analysis and data processing were carried out in a qualitative manner. The research results obtained are, 1) Teachers carry out learning activities both in the classroom and outside the classroom, Utilizing learning media well and adjusting between learning materials with learning methods. 2) In developing the cognitive potential of students in learning PAI the teacher always strives to create a conducive atmosphere so that students do not feel bored in the learning process takes place, and conduct evaluations at the end of each lesson then provide reinforcement for students who answer the questions posed, make personal approaches and give appreciation to students. The implication of the implementation of teaching techniques carried out by PAI teachers has an impact on the success or failure of PAI learning, especially in developing the cognitive potential of grade VII A students in Palopo Muhammadiyah Middle School.